2013
DOI: 10.1258/ar.2012.120355
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of left renal vein entrapment using multidetector computed tomography

Abstract: Left renal vein entrapment is not a rare entity and renal nutcracker phenomenon might be underdiagnosed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 26 publications
(32 reference statements)
0
25
1
5
Order By: Relevance
“…Nutcracker syndrome, an anomaly arising due to compression of the left renal vein between the aorta and the superior mesenteric artery or vertebra, has been reported to lead to increased pressure in the left renal vein and venous congestion in the kidney, and to manifest itself with left flank pain, hypertension or hematuria in some patients presenting with hematuria or flank pain and with no identified underlying pathology capable of accounting for this [4,5,6,7,8,9]. However, there is no information in the literature regarding whether or not congenital renal vein malformations, such as CLRV, RLRV and MRV, lead to hematuria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nutcracker syndrome, an anomaly arising due to compression of the left renal vein between the aorta and the superior mesenteric artery or vertebra, has been reported to lead to increased pressure in the left renal vein and venous congestion in the kidney, and to manifest itself with left flank pain, hypertension or hematuria in some patients presenting with hematuria or flank pain and with no identified underlying pathology capable of accounting for this [4,5,6,7,8,9]. However, there is no information in the literature regarding whether or not congenital renal vein malformations, such as CLRV, RLRV and MRV, lead to hematuria.…”
Section: Discussionmentioning
confidence: 99%
“…Although these renal vein anomalies are generally regarded as following a quiescent course with no clinical findings, there are also case reports and studies that suggest the spontaneous complications of left renal vein anomalies may occur related to the nutcracker syndrome in its different forms [4,5,6,7,8,9]. Various studies have reported that nutcracker syndrome, an anomaly arising as a result of the left renal vein being compressed between the aorta and superior mesenteric artery or vertebra, leads to increased pressure in the left renal vein and venous congestion in the kidney, and this condition manifests itself with left flank pain and hematuria [4,5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NCS is characterized by symptomatic compression of the left renal vein (LRV) between the abdominal aorta posteriorly and superior mesenteric artery (SMA) anteriorly (1-4,52-57). If asymptomatic, it is called nutcracker phenomenon (NCP) (52,56,57). NCS is also known as mesoaortic LRV compression, LRV entrapment syndrome, and "anterior" NCS (1,54,56,57).…”
Section: Ncsmentioning
confidence: 99%
“…If asymptomatic, it is called nutcracker phenomenon (NCP) (52,56,57). NCS is also known as mesoaortic LRV compression, LRV entrapment syndrome, and "anterior" NCS (1,54,56,57). A "posterior" NCS has also been described (approximately 20% of all NCS) cases, in which a circumaortic (17%) or retroaortic (3%) LRV is compressed between the aorta and vertebral body (54,(56)(57)(58).…”
Section: Ncsmentioning
confidence: 99%